Investigation on the influence of whale-watching boats on the respiratory and diving behaviour of Humpback whales (Megaptera novaeangliae) in Skjálfandi Bay, Northeast Iceland. - BOTTONI, VALENTINA (2024)
open The humpback whale (Megaptera novaeangliae) is one of the most abundant species of mysticeti (baleen whales) found around the coast of Iceland, especially in the north-east area. Due to their spectacular aerial behaviours, they are one of the most popular target species of whale watching tours. Nowadays, as the whale watching business is skyrocketing, the concern among researchers is understanding the possible impacts of said human activity on the cetaceans, with a focus on potential behavioural disruption. The present study aims to investigate whether the presence of whale watching boats is affecting the respiratory pattern and diving behaviour of humpback whales in Skjálfandi bay, northeast Iceland. In order to achieve this goal, the study has been carried out focusing on the number of vessels present during each whale sighting and how closely the animals were approached by the boats. Analysis of the records of humpback sightings from the year 2020 to 2024 was done and from the inspection of the respiratory behaviours collected during each whale sighting the time spent diving, the surface time, the number of breaths per surfacing and the breathing rate were calculated. Afterwards, statistical inference was done using linear regression models and generalized linear models. The most interesting results showed signs of vertical avoidance with a statistically significant increase in the time spent diving as both the number of boats increased and the distance from the humpback decreased. Associated with an increase in the diving time, the number of breaths taken for each surfacing decreased as the distance of approach to the animal decreased. As a result, it can be concluded that humpback whales seem to respond to anthropogenic disturbance with vertical behavioural avoidance. The humpback whale (Megaptera novaeangliae) is one of the most abundant species of mysticeti (baleen whales) found around the coast of Iceland, especially in the north-east area. Due to their spectacular aerial behaviours, they are ...